The Role of Angiopoietin-like Protein 3 and Fibroblast Growth Factor 21 to Lipolysis, Inflammation and Insulin Resistance in Indonesian Non-Diabetic Obese Male - Yani Lina; Gatot Susilo Lawrence; Andi Wijaya; Suryani As'ad (The Indonesian Biomedical Journal, 2010)
BACKGROUND: Obesity is commonly associated with a systemic low grade inflammation and insulin resistance state. Although it is still being debated, increased lipolysis is known as one of the risk factors for inflammation and insulin resistance. Two factors already known to affect lipolysis are Angptl3, known as prolipolytic factor, and FGF21, known as antilipolytic factor. The aim of this study was to observe the role of Angptl3 and FGF21 to lipolysis, inflammation and insulin resistance in non diabetic obese male.METHODS: This was an observational study with cross sectional design. One hundred and thirty male subjects aged 30-60 years with non diabetic abdominal obesity characterized by waist circumference 97.32±5.63 cm and fasting blood glucose 90.19±8.78 mg/dL.RESULTS: The results of this study showed a correlation between Angptl3-FFA (r=0.203; p=0.021; R square=0.041; p=0.021), Angptl3-FABP4 (r=0.330; p=0.000; R square=0.109; p=0.000) and Angptl3-TNFα (r=0.288; p=0.001; R square=0.049; p=0.011). There was a correlation between FGF21-FABP4 (r=0.218, p=0.013; R square=0.047, p=0.013) and FGF21 HOMA-IR (r=0.308, p=0.000; R square=0.046, p=0.014).CONCLUSIONS: We conclude that Angptl3 may affect lipolysis and inflammation while FGF21 may affect lipolysis and insulin resistance. The increased FGF21 concentration might occur as a compensation (negative feedback mechanism) to reduce lipolysis and increase insulin sensitivity in non diabetic obese males. Further studies might be needed to observe Angptl3 and FGF21 profile in more severe obese population in Indonesia.KEYWORDS: obesity, lipolysis, inflammation, insulin resistance